Omega-6/omega-3 fatty acid intake of children and older adults in the U.S.: dietary intake in comparison to current dietary recommendations and the Healthy Eating Index - Kelly W. Sheppard; Carol L. Cheatham (Lipids in Health and Disease, 2018)
Abstract Background Omega-6 and omega-3 fatty acids (FAs) and their ratio have been shown to affect cognitive function in children and older adults. With these analyses, we aimed to describe omega-6 and omega-3 FA intake among children and older adults in light of FA intake recommendations and with consideration of overall diet. Methods Data were merged from two cross-sectional studies with 219 children 7 to 12 years old and one longitudinal study with 133 adults 65 to 79 years old. Demographic data, anthropometric data, and Healthy Eating Index scores were used to study relations among the omega-6 to omega-3 FA ratio and age, education, body mass index, and diet quality. FA intake, demographic, and anthropometric data were examined using partial correlations, t-tests, and analysis of variance. Results Most children and adults consumed at least the recommended amount of alpha-linolenic acid (LNA; omega-3) for their age and gender without consuming high amounts of linoleic acid (LA; omega-6), but did not consume sufficient eicosapentaenoic acid (EPA; omega-) and docosahexaenoic acid (DHA; omega-3). The average omega-6 to omega-3 ratios in both groups were lower than previously reported. Eating lower ratios was associated with healthier diets and consuming adequate amounts of several other nutrients. No demographic or anthropometric variables were related to FA intake in children. Adults with a college degree had significantly lower ratios than those without a college degree. Conclusions American children and older adults are able to consume more balanced omega-6 to omega-3 ratios than has been indicated by commodity data. However, very few American children met even the lowest recommendations for EPA and DHA intake. Research is needed to clarify recommendations for the optimal ratio across development, which may aid in increasing EPA and DHA intake and improving health outcomes in the United States. Trial registration ClinicalTrials.gov NCT02199808 13 July 2014, NCT01823419 (retrospectively registered) 20 March 2013, and NCT01515098 18 January 2012.